Development and motion control of spatial serial robotic manipulator under varying disturbances. (12th August 2019) - Epenetus, Alex Barre; CS, Meera; Mohan, Santhakumar; Gupta, Mukul Kumar
Abstract : Purpose: Key challenges in evaluating the performance of a robotic manipulator are disturbances that rise internally and externally. Effects of non-linear disturbances like varying payload and joint friction can adversely affect the tracking performance in a robotic manipulator. This paper aims to discuss motion control of a three-link spatial manipulator using a computed torque observer-based control technique. Design/methodology/approach: The overall motion control problem consists of derivation of kinematic and dynamic model of the manipulator followed by the control design to achieve desired manipulator response. In this study, the manipulator is subjected to uncertain varying load disturbances. The proposed motion controller compensates the effect of the disturbances and guarantees the convergence of tracking error to steady state value. Findings: One major advantage of using observer-based control is positioning accuracy with robustness to parameter uncertainty and fast dynamics response. The performance of the proposed control technique is validated through real-time experiments conducted on the manipulator. The experiment results confirm the superior performance of the control system in achieving perfect tracking. Originality/value: This paper demonstrates an observer-based control technique over a serial spatial manipulator which can be applied different robotic configurations under the effect of varying disturbances.